2020
DOI: 10.3390/ijms21249660
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Fat Oxidation in Mouse Prostate Cancer Decreases Tumor Growth and Stimulates Anti-Cancer Immunity

Abstract: Lipid catabolism represents an Achilles heel in prostate cancer (PCa) that can be exploited for therapy. CPT1A regulates the entry of fatty acids into the mitochondria for beta-oxidation and its inhibition has been shown to decrease PCa growth. In this study, we examined the pharmacological blockade of lipid oxidation with ranolazine in TRAMPC1 PCa models. Oral administration of ranolazine (100 mg/Kg for 21 days) resulted in decreased tumor CD8+ T-cells Tim3 content, increased macrophages, and decreased blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Previous work using the same animal model showed that inhibiting VGSC activity specifically by using TTX injected directly into primary tumours (to avoid systemic toxicity) also suppressed lung metastasis and improved survival by some 20% [ 37 ]. Guth et al showed in the TRAMPC1 genetic mouse model of prostate cancer that ranolazine (i) suppressed tumour growth and (ii) stimulated anti-cancer immunity measured by decreased tumour CD8 + T-cells Tim3 content, increased macrophages and decreased blood myeloid immunosuppressive monocytes [ 38 ]. Finally, Lasheras-Otero et al showed in a mouse model of melanoma that ranolazine suppressed liver metastases [ 39 ].…”
Section: Evidence For the Anti-metastatic Role Of Ranolazinementioning
confidence: 99%
“…Previous work using the same animal model showed that inhibiting VGSC activity specifically by using TTX injected directly into primary tumours (to avoid systemic toxicity) also suppressed lung metastasis and improved survival by some 20% [ 37 ]. Guth et al showed in the TRAMPC1 genetic mouse model of prostate cancer that ranolazine (i) suppressed tumour growth and (ii) stimulated anti-cancer immunity measured by decreased tumour CD8 + T-cells Tim3 content, increased macrophages and decreased blood myeloid immunosuppressive monocytes [ 38 ]. Finally, Lasheras-Otero et al showed in a mouse model of melanoma that ranolazine suppressed liver metastases [ 39 ].…”
Section: Evidence For the Anti-metastatic Role Of Ranolazinementioning
confidence: 99%
“…In addition, exposure to the tyrosine kinase inhibitor, ESK981, decreased tumor growth in prostate cancer cell lines and mouse xenografts by targeting 1-phosphatidylinositol-3-phosphate 5-kinase (PIKfyve), a lipid kinase [ 106 ]. Inhibition of lipid oxidation with ranolazine in the TRAMPC1 mouse model resulted in decreased expression of the immune checkpoint block protein Tim3 in CD8+ cells, increased the content of macrophages in the tumor site, and decreased the number of immunosuppressive monocytes in the blood [ 107 ].…”
Section: Pharmacological Interventions Targeting Lipid Metabolism Aff...mentioning
confidence: 99%
“…In contrast to most neoplasia, which use glycolysis to meet increased energy requirements, the hallmark phenomenon of prostate cancer is slow glycolysis and intensified lipid metabolism [ 25 ]. These cells mainly use β-oxidation of fatty acids (FA) for energy production [ 26 , 27 , 28 , 29 ] and the increased rate of proliferation requires intensive phospholipid (PL) synthesis [ 25 ]. The research group detected higher levels of choline and glycerophosphoetanolamine, which are PLs constituting the cell membrane, in malignant tissue.…”
Section: Genitourinary Malignanciesmentioning
confidence: 99%
“…In this study, the components of this system (carnitine, acetylcarnitine, and hydroxybutyrylcarnitine) showed elevated levels in neoplastic cells ( Figure 3 ). The molecules mentioned previously are candidates for clinical biomarkers of disease aggressivity, metastatic potential, recurrence, prognosis, and survival, in addition to their providing potential therapeutical targets in the future [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Genitourinary Malignanciesmentioning
confidence: 99%